PAC, EDUCAÇÃO E HETERONOMIA CULTURAL - Roberto Leher (Universidade Federal do Maranhão, 2007)
This paper examines the connections between Programa de Aceleração do Crescimento (PAC) and Education using the category of depenclent capitalism. It sustains that from the point of view of the local fractions of internationalized bourgeoisie, the picture of educational apartheid that takes place in the country — as delineated in this paper — is not a substantive problem. Education contributes to governability and to prepare modest schoolarization workers‟ labor force. The study argues that PAC, being part of a larger plan that is redrawing the economical geography of Latin America, will worsen educational picture which is already dramatic. The consequence is a subordinate economy to the dynamic centers of the capitalísm, structured infragmented productive chains, based on intensive use of energy and on highlyexplored labor force. This study defends that as local fractions of the bourgeoisie operate the dependent capitalism in national basis, they cannot be mobilized to do an “educational “revolution like bourgeois fractions did at other countries in past times. lt concludes that the universalization of public education rights will only happen in case social mobilizations exist with enough force to impose defeats to neoliberal hegemony.